(untitled) (Research, Society and Development, 2022)
Objective: was to know the history of breastfeeding, the sociodemographic and obstetric profile among postpartum women attended in a reference public maternity hospital. Methodology: cross-sectional field study with quantitative approach, developed between November 2019 and March 2020, with 300 puerpery hospitalized in a reference public maternity hospital, selected for convenience. Data collected in a form containing questions about sociodemographic, obstetric and breastfeeding information and analyzed descriptively considering the absolute and relative frequencies of the variables. Research approved by the Research Ethics Committee of the Federal University of Maranhão under protocol no. 3,450,563. Results: The puerpery women were between 18 and 30 years old; 61.0% were married or in a stable union; 72.6% attended high school; 65.4% with family income between 1 and 2 minimum wages; 76.0% were housewives; 42.7% had 2 children; 99.7% had prenatal care; 65.4% had six or more consultations; 49.3% were oriented about breastfeeding during prenatal care; 76.7% have breastfed before; 60.0% had no difficulties to breastfeed and the others reported a complaint of little milk (22.0%), nipple fissure (15.4%), complained of having weak milk (1.6%) and felt pain (1.0%). Conclusion: It was evidenced the importance of the use of educational activities aimed at breastfeeding by health professionals who provide prenatal, childbirth and puerperium care, aiming to contribute to the mothers being able to breastfeed, thus reducing the rates of early weaning.